Spontaneity and Conscious Action in the Self-Organization of Society: Axiological Aspect - Komarova, Irina (Problemos, 2001)
The article is deals with the problem of supplementing the spontaneous synergetic and rationally purposeful self-organization of the society with axiological factors. The author maintains that to raise the society to the new level of the social organization it is necessary to consider values as the unity of the end and the mean; the choice of necessary components for the new level is determined by the elements of the hierarchy of the value. Stability is the main criteria that rules the process of the social self-organization.